Autism Spectrum Disorder and Harassment: An Application of Attribution Theory - Mogavero, Melanie Clark; Hsu, Ko-Hsin (International Journal of Criminology and Sociology, 2018)
The social and communication impairments among those with autism spectrum disorder (ASD) may result in some unknowingly harassing someone while pursuing a romantic interest. Weiner’s (1974) Attribution Theory suggests that when people attribute negative behaviors to a condition, they perceive less controllability, and evoke fewer negative emotions and punishments. The authors applied Attribution Theory using a sample of 545 undergraduates who received one of three vignettes depicting a male harassing a female romantic interest (no mention of ASD, mention of ASD, mention of ASD and difficulty with social relationships and communication). Those who received the vignettes that mentioned the perpetrator had ASD perceived the behavior as less controllable and fewer supported punishment. The results demonstrate support for disclosing one’s ASD diagnosis and communicating any social or communication difficulties to others in the event there are miscommunications that could lead to punitive consequences.